A series of Rb4Ln2(P2S6)(PS4)2 (Ln = La, Ce, Pr, Nd, Sm, Gd) rare earth thiophosphates with two distinct thiophosphate units [PVS4]3− and [PIV2S6]4−. Issue 5 (14th January 2021) - Kutahyali Aslani, Ceren; Breton, Logan S.; Klepov, Vladislav V.; zur Loye, Hans-Conrad
Abstract : A new series of rare earth thiophosphates, Rb4 Ln2 (P2 S6 )(PS4 )2 (Ln = La, Ce, Pr, Nd, Sm, Gd), containing two unique thiophosphate motifs, [P V S4 ] 3− and [P IV 2 S6 ] 4−, were synthesized using the high temperature molten flux crystal growth method by RbBr flux. Abstract : A series of rubidium rare earth thiophosphates with the formula Rb4 Ln2 (P2 S6 )(PS4 )2 (Ln = La, Ce, Pr, Nd, Sm, and Gd) were synthesized using the high temperature molten flux crystal growth method utilizing a RbBr flux. Single crystals of all title compounds, as well as phase pure powders of the La-, Ce-, and Sm-containing compositions, were obtained. Single crystals of the title compounds were characterized by single crystal and powder X-ray diffraction for structure and phase identification. Rb4 Ln2 (P2 S6 )(PS4 )2 crystallizes in the monoclinic crystal system adopting the P 21 / n space group for the large rare earths (Ln = La, Ce, Pr) and the C 2/ c space group for the smaller rare earths (Ln = Nd, Sm, Gd). This Rb4 Ln2 (P2 S6 )(PS4 )2 series is a rare example of thiophosphates containing both tetrahedral [P V S4 ] 3− and dimeric [P IV 2 S6 ] 4− thiophosphate units that, in this structural family, link corrugated rare earth sulfide chains into sheets. The band gaps of the materials were determined from UV–Vis data and the fluorescence spectrum of Rb4 Ce2 (P2 S6 )(PS4 )2 was collected. Optical band gaps were estimated to be 2.9 and 2.4 for the Nd and Sm analogues, respectively.